Emblèmes d'espace dans la poésie de Maurice Carême - Tóth, Ágnes (Verbum – Analecta Neolatina, 2012)
Geometrical spaces are saturated with experiences and emotions, their metaphorical meanings are supported by individual and collective experiences. The spaces created and wandered by the poet's imagination are places of our spiritual space experience. In the poems of Maurice Carême, a 20th century Belgian poet, we can walk along such objective-spiritual spaces. These emblematic fields are not only sceneries but also places of poetical self-search: poetic life, childhood, losing and finding, which can be interpreted from a space–poetic-self relationship. In the present paper, I have classified and interpreted the spatial emblems appearing in Carême's poetic works along horizontal and vertical lines. These spaces—space emblems—embody ambitions, desire, different ways of behaviour, namely representations of relations. At horizontal level, this relationship is represented by an in-out dialectics: house, castle, nest, garden (inwardness), walls (protects but separates), window, threshold, door, bridge, path are toposes which provide spatial transition. The spatial emblems supporting the vertical motion, the up-down dialectics: ladder, stairs, tower, well. These spatial toposes create a transition between the three levels of the world: Underworld, Earth, Heaven. Their presence in the poetic imagery indicates the primeval desire of people for transcendent experience.